Plan de negocios para la implementación de un centro deportivo para la ejercitación física entre amo y su perro - Herrera Regalado, Yadira Elizabeth (2016)
This business plan corresponds to the creation of a Center for physical exercise for dogs and their owners. The current pace of life makes them sedentary people, and their pets have the same problem. Currently Quito is a city that has a tendency to play sports and kept healthy, but people neglect their dogs which need 30 minutes of physical activity. The industry that “Canientrenamiento” part is corresponding to R: Arts, Entertainment and Recreation and that is not taken over. The idea of exercising with your dog is not common in this country. It is most people do not know they can do exercises with his dog but being able to unify the time to exercise them is innovative and captivating. There will qualified coaches with experience in joint exercise, also a medical assistant in case someone gets hurt, veterinarian, pet-shop, and bar. Everything for the complete care of people and their dogs. Always users have a person to help people with all their questions and assist them. This center focuses on men and women who play sports at least three times a week. They have to live in Quito, to have dogs and belonging to the upper and upper middle classes. It was noted that people felt valleys preference for location and that is how it was designed. It is to provide various sports such as: Canicross, bikejoring, Doga (yoga with dogs), Frisbee, Ball, Agility, and Training, so users will have several options to be exercised at different schedules and with varying difficulty for sport. It is a way out of the routine, replace traditional gyms and given the opportunity to be healthy people with vitality and their dogs have the same living conditions without using overtime.